Pengaruh Lama Perendaman dan Konsentrasi ZPT Sintetis Terhadap Pertumbuhan Tanaman Bunga Wijaya Kusuma (Epiphyllum oxypetalum) - Maula, Nizma Ma'rifatul; Purnomo, Sulistyo Sidik; Rahayu, Yayu Sri (UNIVERSITAS LABUHANBATU, 2023)
The wijaya kusuma plant is included in the cactus type ornamental plant which has high economic value and it’s profitable. High demand makes the need for wijaya kusuma plants require fast and efficient method of propagation. Plants propagation by cuttings relatively fast and practical to produce plants that are ready for sale. One step to accelerate growth of roots and shoots is by adding synthetic ZPT and soak before planting. The aim of this study was to obtain concentration of synthetic ZPT that gave the best growth of wijaya kusuma (Epiphyllum oxypetalum) cuttings for each long soaking. This experiment was carried out in Sukamulya Viillage, Sukatani, Bekasi Regency, West Java. The experiment was carried out in August-November 2022. The research used was an experimental method using factorial 3x3 Randomized Block Design (RBD), The first factor is the long soaking, there are 3 levels, namely 11 (150 minutes), l2 (180 minutes), and l3 (210 minutes) The second factor has 3 levels, namely k1 (150 ppm), k2 (200 ppm), and k3 (250 ppm). There was an interaction effect between long soaking and synthetic ZPT concentration on root length and shoot length at 7 mst, 8 mst and 10 mst. Treatment of l2k1 (long soaking 180 minutes+ZPT concentration 150 ppm) resulted in an average shoot length longest at 10 mst of 20,500 cm Treatment l1k1 (long soaking 150 minutes+ZPT concentration 150 ppm) and resulted in the longest root average of 11.958 cm.Key words: soaking, concentration ZPT, wijaya kusuma.